Mutagenic and antimutagenic properties of some lichen species grown in the Eastern Anatolia Region of Turkey - Aslan, A.; Gulluce, M.; Agar, G.; Karadayi, M.; Bozari, S.; Orhan, F. (Цитология и генетика, 2012)
All the methanol extracts did not show mutagenic activity in Ames/Salmonella and Z. mays MI test systems. Furthermore, some extracts showed significant antimutagenic activity against 9-AA in Ames test system. Inhibition rates for 9-AA mutagenicity ranged from 25.51 % (P. furfuracea – 0.05 μg/plate) to 66.14 % (C. islandica – 0.05 μg/plate). In addition, all of the extracts showed significant antimutagenic activity against sodium azide (NaN₃) mutagenicity on MI values of Z. mays. Целью работы было изучить мутагенный и антимутагенный потенциал метанольных экстрактов Cetraria islandica (L.) Ach. (Parmeliaceae), Pseudevernia furfuracea (L.) Zopf (Parmeliaceae) и Xanthoparmelia somloënsis (Gyeln.) Hale (Parmeliaceae) – лишайников из восточной части Турции. Ни один из экстрактов не показал мутагенной активности в тестах Эймса и Z. mays MI. Более того, некоторые экстракты проявляли заметную антимутагенную активность против 9-амино-акридина в тесте Эймса. Уровень ингибирования варьировал от 25,51 % (P. furfuracea) до 66,14 % (C. islandica). Кроме того, все экстракты проявляли значительную антимутагенную активность против азида натрия в Z. mays MI тесте. Все экстракты могут считаться генотоксично безопасными в исследованных концентрациях.